Trade, Investment and Development in the Middle East and North Africa : Engaging with the World - World Bank (Washington, DC, 2013)
The book describes why expanding trade, and investment is vital for the Middle East and North Africa region. The greatest economic challenge is to create enough jobs for its rapidly growing labor force, which is increasingly young, and educated, to ward off threats to social, and political stability, inherent in high unemployment rates. This effort requires higher, and more sustainable, economic growth than has been achieved in the past two decades. Expanding trade, and private investment offers the best hope. The potential is enormous, given the region's human resources, skills, location, and opportunities. The book also analyzes why the region has yet to tap fully into the rich stream of global commerce, and investment - and the measures needed to do so, including improvements in the domestic investment climate, and reforms in the policies of the region's trading partners.